Correlating physiological responses of exergaming boxing in different body positions and disability / Nor Aina Mohd Jai - Nor Aina, Mohd Jai (2021)
Physiological responses during exergaming may be affected by the position of gameplay and physical disability. This study aims to validate the correlations between heart rate and rating of perceived exertion coefficients when playing a moderate-vigorous intensity exergame among the able-bodied and wheelchair-user populations to formulate a possible regression model based on confounding factors, such as the position of gameplay, disability, age, or body mass index. To do this, the Sony PlayStation 3® consoles, along with its two Move motion controllers; Sony Eye Camera and Sports Champion 2® software, were selected as the modality of choice. A total of 45 participants were recruited and divided into able-bodied (mean age of 25.1 (2.95)) and wheelchair-user (mean age of 30.3 (10.3)). The able-bodied participants performed the Move Boxing in sitting position for 10 minutes and standing position for 10 minutes, with at least a day gap. Wheelchair-users performed the Move Boxing while seated in their wheelchairs for 10 minutes. HR measurements were obtained at rest and during gameplay. RPE was assessed using Borg’s modified (1−10) and original (6−20) scales. All data were expressed as mean (standard deviation) (SD). The significance level was set as a priority at P=0.05. SPSS (Version 25.0) was utilized to perform all statistical analyses. Normality tests and statistical tests were conducted, including paired-sample t-test, bivariate Pearson’s correlation, and Spearman’s rho correlation, to analyse the results. The mean HR was significantly higher when the able-bodied users performed exergaming in the standing position (130.79 (23.18) beats per minute (bpm)) compared to the sitting position (116.46 (19.08) bpm) (p ≤0.05), and more similar to those obtained by wheelchair-users while playing on their wheelchairs (130 (14) bpm). There was a significant correlation between HR and RPE values while playing boxing exergame in the standing position. For wheelchair-users, HR elevation also correlated well with both Borg’s RPE original and modified scales during exergaming while being seated in their wheelchairs. A regression model that can be fitted into an equation to predict HR from reported RPE was derived from the significant values of Pearson’s correlation. The formula extracted from the linear regression models provided reliable predictions in estimating HR from reported RPE while boxing exergaming in a standing position and being seated in wheelchairs for future research works.